Profile of Students’ Physics Problem Solving Skills and Problem Based Learning Implementation Supported by Website on Gas Kinetic Theory - Pristianti, Mila Candra; Prahani, Binar Kurnia (Jurnal Pendidikan Progresif, 2022)
Profile of students’ physics problem-solving skills and problem based learning implementation supported by website on gas kinetic theory. Objectives: To analyze physics problem solving skills as a consideration in the implementation of a website-based PBL model on kinetic theory of gases. Methods: The research subjects were 162 high school students in class XI in Madiun Regency based on purposive sampling. Data collection were using problem-solving skills test ACCES indicators, student questionnaires, physics teacher interviews. Data were analyzed descriptive qualitative. Findings: The level of problem-solving skills in the kinetic theory of gases is still low, 159 students in low category, 3 students in medium category. On average students only answered questions in the E-Execute the solution. Conclusion: Students are not used to solving questions with ACCES indicators. Students tend to learn by memorizing formulas. So, the website-based PBL model can be applied to improve students' problem solving skills. Keywords: problem solving skills, problem based learning, Gas kinetic theory.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202229